1991
DOI: 10.1203/00006450-199109000-00009
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I Stimulates Tropoelastin Synthesis in Neonatal Rat Pulmonary Fibroblasts

Abstract: ABSTRACT. We have examined the effect of IGF-I on tropoelastin (TE) synthesis in cultured rat neonatal pulmonary fibroblasts, because this growth factor has been shown to stimulate TE synthesis in vascular smooth muscle cells. IGF-I stimulated TE and total protein synthesis in a dose-dependent manner even when cells were cultured in the medium supplemented with 0.5% FCS. The maximal stimulation was at IGF-I concentration 500 ng/mL and was an increase of 86 f 14 and 35 f 5% for TE and estimated total protein sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
18
1
Order By: Relevance
“…One prominent study reported tissue specificity for the inductive effects of IGF1 on elastin expression, with a lack of response in lung fibroblasts (52). However, an earlier study suggested some potential elastogenic effects of IGF1 in lung fibroblasts (53). We observed an inductive response that was greater than that observed for other physiological inducers of lung fibroblast elastin gene expression, such as TGFb or retinoic acid (54,64).…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…One prominent study reported tissue specificity for the inductive effects of IGF1 on elastin expression, with a lack of response in lung fibroblasts (52). However, an earlier study suggested some potential elastogenic effects of IGF1 in lung fibroblasts (53). We observed an inductive response that was greater than that observed for other physiological inducers of lung fibroblast elastin gene expression, such as TGFb or retinoic acid (54,64).…”
Section: Discussioncontrasting
confidence: 45%
“…Conversely, we found changes in the expression of multiple paracrine factors from AT2 cells, including the elastogenic molecule, Igf1 (53,73,74), and its binding protein, Igfbp2. Interestingly, lung expression of IGF1/IGF1R has been demonstrated (49), and deficiency in either IGF1 or IGF1R leads to abnormal lung development (50,64).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It is noteworthy that IGF-I signaling is a well-established determinant of longevity (29,57). While IGF-I is known to regulate antioxidant defense and cellular stress response systems, it is also known to stimulate Eln expression in neonatal pulmonary fibroblast cells (52). In the present study, differences in IGF-I signaling between B6 and D2 strains at 2 mo of age were observed with respect to the expression of Igfbp2, Igfbp4, and Pik3r1 (Supplemental Table S3).…”
Section: Discussionmentioning
confidence: 54%
“…Here, the controversy of IGF stimulation of pulmonary fibroblast elastogenesis and its functioning via epithelial-mesenchymal interactions is illustrative. Noguchi and Nelson (1991) have observed an elastogenic effect of IGF in pulmonary fibroblasts of 7-day-old rats (the period of optimal elastogenesis) but, unfortunately, they use supra-physiological concentrations, in the view of Rich et al (1992). In contrast, the latter have found no elastogenic response to physiological concentrations but, in their studies, fibroblasts are isolated from 2-to 3-day-old rats (Rich et al.…”
Section: The Functional Levelmentioning
confidence: 91%